The Effect of Left Temporal EEG Neurofeedback Training on Cerebral Cortical Activity and Precision Cognitive-Motor Performance - Lo, Li-Chuan; Hatfield, Bradley D.; Janjigian, Kiersten; Wang, Yung-Shun; Fong, Dong-Yang; Hung, Tsung-Min (Research quarterly for exercise and sport, 2025)
Objectives: The present study employed individualized magnitudes of electroencephalographic (EEG) alpha (8–12 hz) power in the left temporal (T3) region as a neurofeedback target parameter during the aiming period in pre-elite air pistol shooters to determine its effectiveness on cerebral cortical activation and performance accuracy compared to physical skill training, only. Method: Shooting scores and EEG activity in the left and right temporal regions were collected from 20 healthy air pistol shooters (10 assigned to neurofeedback training) before and after a 16-session intervention completed within 6 weeks. Specifically, EEG low-alpha (8–10 hz), high-alpha (10–13 hz) power, and coherence obtained at the T3-Fz and T4-Fz recording sites over three consecutive 1-s intervals prior to trigger pull, were subjected to three separate 2 × 2 × 2 × 3 (Group x Hemisphere x Time x Epoch) ANOVAs. Results: The neurofeedback group exhibited elevated low- and high-alpha EEG power across both temporal regions, but no differences in EEG broad-band alpha coherence, accompanied by enhanced performance after the intervention compared to the control group. Conclusions: The findings support the influence of neurofeedback training on cerebral cortical arousal and performance of a precision-aiming task, however, the influence of the neurofeedback on brain dynamics (i.e. alpha power) extended beyond the targeted region as a nonspecific manifestation of cerebral cortical inhibition leading to neural efficiency at the homologous sites.